Differences in Aroma Quality of Different Types of Jinmudan Tea Made from Tea Leaves Harvested in Summer and Autumn - TANG Mengting, LIAO Xiansheng, WU Xianshou, WEI Mingxiu, ZHENG Yucheng, JIN Shan, ZHANG Jianming, YE Naixing (Shipin Kexue)
In this study, the tender shoots of ‘Jinmudan’ tea plants harvested in summer and autumn were processed separately into green tea, yellow tea, white tea, oolong tea and black tea. Headspace-solid phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) was used to determine and analyze the volatile metabolites in the 10 tea samples. The results showed that 522 volatile metabolites were identified in the summer tea, mainly including terpenes, esters and alcohols, and 502 volatile metabolites in the autumn tea, mainly including terpenes, esters and heterocyclic compounds. The analysis of odor activity value (OAV) showed that β-ionone, α-ionone, decanal, methyl benzoate and geraniol were the key aroma substances of Jinmudan green tea; β-ionone, 2-ethoxy-3-methylpyrazine, decanal, methyl benzoate and geraniol were the key aroma substances of Jinmudan yellow tea; geraniol, phenylacetaldehyde, methyl salicylate (E)-linalool oxide, and 2-ethoxy-3-methylpyrazine were the key aroma substances of Jinmudan white tea; indole, methyl benzoate, phenylacetaldehyde, geraniol, and (E)-linalool oxide were the key aroma substances of Jinmudan oolong tea; geraniol, linalool, phenylacetaldehyde, methyl benzoate, and methyl salicylate were the key aroma substances of Jinmudan black tea. The contribution, type and quantity of aroma substances in the autumn tea were greater than those in the summer tea. The OAV of 42 key aroma substances such as geraniol, methyl salicylate and phenylethanol in the autumn tea samples were higher than those in the summer tea samples. Overall, flowery aroma was the major aroma type of Jinmudan tea, and the aroma quality of the autumn tea was better than that of the summer tea. Totally 14 volatile metabolites such as geraniol, linalool, 2-ethoxy-3-methylpyrazine and methyl benzoate were the key aroma substances of the ‘Jinmudan’ tea variety.